LIBS analysis of samples from the COMPASS vacuum chamber after liquid metal experiments – Li campaign. (December 2020) - Veis, P.; Atikkuke, S.; Marin Roldan, A.; Dwivedi, V.; Veis, M.; Barton, P.; Jerab, M.; Dejarnac, R.
Highlights: Quantitative elemental composition of Li-based coating on screws by CF-LIBS. Li, B, C, Fe, Na, K, Mg, Ca, and Si have been observed in the LIBS spectra. The electron temperature has been evaluated using multi-elemental SB plots. The electron density was obtained from the Stark broadening of the Hα line. Evaporated/redeposited Li in the COMPASS vacuum vessel information is provided. Abstract: To overcome the erosion of the plasma-facing materials (PFMs) inside a fusion reactor, liquid metals such as lithium or tin are being explored as potential PFMs in fusion reactors due to their several advantages such as self-repair or high-power exhaust capability. Lithium can reduce the oxygen and carbon impurity contamination by chemically binding these species to the wall. Thus, experiments of power handling performance with a special liquid metal (Li) divertor module based on the capillary porous system technology were performed in the tokamak COMPASS. The elemental analysis of 14 screw samples located around the vacuum vessel provides information about the migration of evaporated/redeposited liquid elements. The main goal of this work is to characterize and quantify screws containing Li-based coating by LIBS by measuring the quantitative elemental composition. The studied samples were Li-coated Ni-Cr-based screws. The laser ablation was performed in air at atmospheric pressure using a 5 ns pulse Nd:YAG laser at 1064 nm. Suitable Li I, Ca I-II, and Fe I spectral lines were employed for the evaluation of the electron temperature of the plasma using multi-elemental Saha-Boltzmann plots. The electron density was obtained from the Stark broadening of the Hα spectral line. The elemental content of each sample was then obtained by calibration-free LIBS (CF-LIBS).